INTEGRATION OF THE ORGANIZATIONAL CULTURE AND HR PRACTICES OF THE SVD EDUCATIONAL INSTITUTIONS IN THE PHILIPPINES TOWARDS A MODEL OF INSTITUTIONALIZED HR POLICY: A LITERATURE REVIEW - Renato A. Tampol; Hector M. Aguiling (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Human Resource (HR) policy is not a one-size-fits-all approach. Underpinnings and reasons for the development of HR policy may be parallel for most organizations, regardless of type and nature, but pertinent factors considered for such development may vary. The most common yet influential amongst the factors is the culture of the organization. Organizational culture is one of the most researched topics in organizational studies. It had been used as a construct in various settings, even in the education landscape. Previous studies show that organizational culture impacts the HR practices and policies of organizations. However, the literature is silent on its application in Catholic educational institutions’ HR practices and policies in the Philippines. This study used literature review as its method to integrate organizational culture and HR practices toward institutionalizing their HR policies. Society of Divine Word (SVD) educational institutions within the Philippines A standard HR Policy is aimed to be used across all SVD schools in the Philippines.